Characteristics of warming and humidification in the Yellow River's upper reaches and their impact on surface water resources - Jinhu Yang; Qiang Zhang; Ping Yue; Pengling Wang; Xinyu Duan; Jinyu Zhang; Zhuoqi Liang; Guoyang Lu; Xuying Sun; Xin Wang; Chenxi Liu (International Journal of Climatology, 2023)
Based on multi‐source data, including observation, analysis, model calculation, satellite remote sensing, and scenario estimation data, this study has systematically analysed the warming and dry–wet change characteristics of the Yellow River's upper reaches in the last 60 years. The causes and features of the current warming and humidification and their impact on surface water resources are also discussed. This study found that since 1961, the average temperature in the Yellow River's upper reaches has increased at a rate of 0.37°C/10a, which is more significant than the increases observed for the world, China, and even northwest China in the same period. At the beginning of this century, the rate of change in precipitation in the Yellow River's upper reaches reversed direction from decreasing to increasing, with a significant increase (35 mm/10a) since 2000. Therefore, climate change has shown a significant warming and humidification trend in the upper reaches of the Yellow River. From the dynamic change perspective, the Yellow River's upper reaches were warming and drying in each climatic period from 1961 to 2010; however, the tendency towards dryness slowed period by period. In contrast, the region showed consistent warming and humidification from 1991 to 2020. From the perspective of multiple time scales, the change in average temperature is mainly dominated by the multi‐decadal scale. In contrast, precipitation is dominated by interannual change. The increase in the multi‐decadal component in average temperature and precipitation explains the current warming and humidification. Precipitation changes in the upper reaches of the Yellow River Basin are mainly affected by the westerly circulation, the East Asian summer monsoon, and the South Asian summer monsoon circulation systems. However, precipitation was affected by different circulation factors on different time scales. On an interannual scale, it was mainly affected by the South Asian summer monsoon circulation. On an interdecadal scale, it was mainly affected by the westerly wind and the East Asian summer monsoon circulation. On a multi‐decadal scale, it was jointly influenced by the westerly wind, the East Asian summer monsoon, and the South Asian summer monsoon circulation. Under the control of multi‐decadal synergistic enhancement of the westerly, the East Asian summer monsoon, and the South Asian summer monsoon circulations, the vertical field shows an abnormal upward movement. There has been a significant abnormal easterly and southerly airflow that transports water vapour, and cold air is transported along the northwest airflow at the back of the Mongolian cyclone, which makes the climate in the upper reaches of the Yellow River more humid. The warming and humidifying of the upper reaches of the Yellow River has significantly increased runoff and lake area and significantly degraded the frozen soil. The surface water budget in the Yellow River's upper reaches has significantly responded to the current warming and humidification. The actual surface evapotranspiration and surface runoff increased significantly, but the net surface water budget still showed a decreasing trend. The increase in precipitation did not change the surface water deficit.